2018
DOI: 10.29374/2527-2179.bjvm045118
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Flavivirus in horses in Chaco, Argentina. Circulation during 2013-2014

Abstract: Flaviviruses are responsible for several emerging mosquito-borne diseases in Argentina and in the Americas. Some of these diseases are zoonoses and were detected in recent years: West Nile virus (WNV) and Saint Louis encephalitis virus (SLEV) among them. WNV originated in Africa was detected for the first time in America in 1999 and it was first isolated from diseased and dead horses in 2006 in Argentina. Neutralizing antibodies from wild birds, humans and horses have been also detected in later years. SLEV re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…As stated, this is the first report of antibody seroprevalence against Flavivirus in blood donors using a biological assay such as PNRT. Since the close antigenic association between Flaviviruses generates a cross‐reactive immune response 11 and considering their overlapping distribution in the region, 2,5,7,8,23–25 which increases the likelihood of exposure to multiple viruses of the same genus, PNRT remains the only assay that allows differentiating serological cross‐reactivity that could impair a real estimate of the seroprevalence values. Seroprevalence of arboviruses in blood donors provides important information to estimate viral circulation in the general population and is essential for understanding the risk of transmission through blood transfusions and developing effective strategies to prevent transmission of these viruses.…”
Section: Discussionmentioning
confidence: 99%
“…As stated, this is the first report of antibody seroprevalence against Flavivirus in blood donors using a biological assay such as PNRT. Since the close antigenic association between Flaviviruses generates a cross‐reactive immune response 11 and considering their overlapping distribution in the region, 2,5,7,8,23–25 which increases the likelihood of exposure to multiple viruses of the same genus, PNRT remains the only assay that allows differentiating serological cross‐reactivity that could impair a real estimate of the seroprevalence values. Seroprevalence of arboviruses in blood donors provides important information to estimate viral circulation in the general population and is essential for understanding the risk of transmission through blood transfusions and developing effective strategies to prevent transmission of these viruses.…”
Section: Discussionmentioning
confidence: 99%
“…Although the number of field studies dedicated to the pathogens circulating in this province remains low, it may be noted that numerous vector-borne diseases have already been reported. These include equine infectious anaemia (EIA) (De la Sota et al, 2005), West Nile fever (WNF) (Oria et al, 2018), surra (Santa Cruz et al, 2013, equine piroplasmosis (Babesia equi) (Holman et al, 1998), Eastern equine encephalomyelitis (EEE), Venezuelan equine encephalitis (VEE) and Western equine encephalomyelitis (WEE) (Monath et al, 1985).…”
Section: Short Communicationmentioning
confidence: 99%
“…WNF was first detected in Argentina from diseased and dead horses in 2006 (Chancey et al, 2015) and, since then, its circulation has been reported in different provinces in Argentina, including Chaco (Oria et al, 2018). Given the abundance of Culicidae (vectors of WNF) and birds (hosts, natural reservoir) in this region (Campbell et al, 2002), there appears to be a major risk of this virus being transmitted to incidental dead-end hosts represented by horses (and potentially humans).…”
Section: Short Communicationmentioning
confidence: 99%